PENGARUH PASAR BUDAYA TERHADAP KEMAMPUAN ETNOMATEMATIKA PADA ANAK USIA 5-6 TAHUN DI TK AL-HUSNA PEKANBARU - Desyi Purnama Putri; Ria Novianti; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims (1) to determine children's ethnomathematics abilities before being treated at the Cultural Market in children aged 5-6 years at Kindergarten Al-Husna Pekanbaru. (2) To find out children's Ethnomathematics abilities after being treated at the Cultural Market in children aged 5-6 years at TK Al-Husna Pekanbaru. (3) To find out whether there is an influence of the Cultural Market on Ethnomatematics Ability in children aged 5-6 years at TK-Al Husna Pekanbaru. This research is a quantitative experimental research using a one group pretest posttest design. The study population was 17 children aged 5-6 years at TK Al-Husna Pekanbaru, the sample used was 17 children. The data collection carried out in this study was by observing the pretest and posttest. The data analysis technique in this study used the t-test using the SPSS version 23 program. Based on the normalized gain, there is a significant effect. When researchers used the Cultural Market Role Playing Method to improve Ethnomatematics Ability in children aged 5-6 years at TK Al-Husna Pekanbaru by 65.34%. Referring to the results of using the G formula, it can be seen that the category of increase is 65.34% in the medium category. So it can be concluded from the results of this study that there is a significant influence in developing Ethnomatematics Ability using the Cultural Market Role Playing Method in children aged 5-6 years at Al-Husna Kindergarten PekanbaruKeywords: Cultural Market, Ethnomatics